Liposarcoma of the Spermatic Cord: A Case Report - M. S. Papageorgiou; G. Dadakas; K. Donev (Case Reports in Medicine)
Liposarcomas are malignant tumors derived embryologically from mesodermal tissues. An unusual site of presentation is the spermatic cord, presenting as an inguinal or scrotal mass. We report a rare case of a liposarcoma of the spermatic cord, mimicking a testicular tumor. The patient was operated, and an orchidectomy, including the tumor, was performed. To our knowledge, there are about 185 similar cases reported in the literature.